A colorimetric detection of acrylamide in potato chips based on nucleophile-initiated thiol–ene Michael addition. Issue 3 (24th December 2015) - Hu, Qinqin; Fu, Yingchun; Xu, Xiahong; Qiao, Zhaohui; Wang, Ronghui; Zhang, Ying; Li, Yanbin
Abstract : A visible, highly sensitive colorimetric biosensor based on thiol–ene Michael addition reaction was first reported to detect acrylamide (AA) in potato chips. Abstract : Acrylamide (AA), a neurotoxin and a potential carcinogen, has been found in various thermally processed foods such as potato chips, biscuits, and coffee. Simple, cost-effective, and sensitive methods for the rapid detection of AA are needed to ensure food safety. Herein, a novel colorimetric method was proposed for the visual detection of AA based on a nucleophile-initiated thiol–ene Michael addition reaction. Gold nanoparticles (AuNPs) were aggregated by glutathione (GSH) because of a ligand-replacement, accompanied by a color change from red to purple. In the presence of AA, after the thiol–ene Michael addition reaction between GSH and AA with the catalysis of a nucleophile, the sulfhydryl group of GSH was consumed by AA, which hindered the subsequent ligand-replacement and the aggregation of AuNPs. Therefore, the concentration of AA could be determined by the visible color change caused by dispersion/aggregation of AuNPs. This new method showed high sensitivity with a linear range from 0.1 μmol L −1 to 80 μmol L −1 and a detection limit of 28.6 nmol L −1, and especially revealed better selectivity than the fluorescence sensing method reported previously. Moreover, this new method was used to detect AA in potato chips with a satisfactory result in comparison with the standard methods based on chromatography, which indicated that the colorimetric method can be expanded for the rapid detection of AA in thermally processed foods.